2000
DOI: 10.4049/jimmunol.165.5.2331
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD7 Delivers a Pro-Apoptotic Signal During Galectin-1-Induced T Cell Death

Abstract: Galectin-1, an endogenous lectin expressed in lymphoid organs and immune-privileged sites, induces death of human and murine thymocytes and T cells. Galectin-1 binds to several glycoproteins on the T cell surface, including CD7. However, the T cell surface glycoprotein receptors responsible for delivering the galectin-1 death signal have not been identified. We show that CD7 is required for galectin-1-mediated death. This demonstrates a novel function for CD7 as a death trigger and identifies galectin-1/CD7 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
1
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(181 citation statements)
references
References 37 publications
(38 reference statements)
5
169
1
6
Order By: Relevance
“…It was reported that CD7 delivers a proapoptotic signal during galectin-1-induced T-cell death. 10 Furthermore, CD4 þ CD7 À leukemic T cells from patients with Sezary syndrome are protected from galectin-1-triggered T-cell death. 11 It has also been shown that survival of acute myeloid leukemia cells requires phosphatidylinositol 3-kinase (PI3K) activation.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that CD7 delivers a proapoptotic signal during galectin-1-induced T-cell death. 10 Furthermore, CD4 þ CD7 À leukemic T cells from patients with Sezary syndrome are protected from galectin-1-triggered T-cell death. 11 It has also been shown that survival of acute myeloid leukemia cells requires phosphatidylinositol 3-kinase (PI3K) activation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated reversal of galectin-1 resistance in the CD7 Ϫ Sezary cell line Hut78 by expressing CD7 in these cells (36). This implied that all other components of the galectin-1 death pathway besides CD7 were present in Hut78 cells.…”
Section: Discussionmentioning
confidence: 94%
“…1B) indicates that Sezary cells are exposed to galectin-1 in vivo. We hypothesized that Sezary cells may resist galectin-1-mediated apoptosis either because the malignant cells do not express CD7 that is essential for galectin-1-mediated apoptosis (36) or because PNA Ϫ Sezary cells have aberrant cell surface glycosylation that contributes to decreased galectin-1 sensitivity. To examine the relationship between CD7 expression, cell surface glycosylation, and susceptibility to galectin-1, we analyzed cell surface glycosylation and CD7 expression of four Sezary cell lines, Hut78, MyLa 2059, HH, and SeAx/i.…”
Section: Cell Surface Phenotype Of Sezary Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that another human T cell line, HuT-78, was totally resistant to Tet-mediated cytotoxicity (unpublished observations). The HuT-78 T cell line has many characteristics that differ from those of other commonly used T cell lines, such as much lower expression of CD2, CD4, and CD45 as well as much higher resistance to anti-Fas-and TNF-␣-mediated cell death (34,35). The signaling pathway that mediates Tet-induced cytotoxicity may be altered in this particular cell line.…”
Section: Tet-induced Cell Death Appeared To Be Highly Specific Towardmentioning
confidence: 99%